(untitled) (Fiep Bulletin - online, 2011)
Programs with a focus on promoting and increasing physical activity are remarkable effectiveness and relevance of social importance. Based on successful models already in Brazil this project called Orientation physical exercise is being deployed in the city of Parintins - AM. It aims to guide and encourage the regular and proper exercise, combat sedentary lifestyles and assist in the prevention and treatment of chronic non-degenerative diseases. In this first year of implementation and significant results have a very good involvement from both the public and the academics who contributed to the establishment and consolidation of project which today represents an important achievement in physical education in the ICSEZ Parintins. The step activities, localized exercise, stretching and guided walk out has contributed much to the people engage in physical activity, improve their physical fitness to perform activities of daily life by providing health and welfare for these individuals. We also stress that this space used for conducting the activities mentioned above as well as innovative for this city, shows an ongoing commitment to the search for physical education geared toward meeting the desires of the community by encouraging people to adopt a healthy lifestyle and to combat the incidence of chronic degenerative diseases that affect large-scale population.